Anode active material, method for producing anode active material, anode composition, anode for lithium secondary battery including the same, and anode including the same
Patent Information
- Application Number
- JP2024546180
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-11
AI Technical Summary
【0018】 本発明の一実施態様による負極活物質の場合、従来の粉砕式加工法とは違って、シランガスと酸を反応させる化学的方法の反応条件を制御して生成するもので、それによって所定範囲の平均粒径(D50)および結晶粒径を満たすことを特徴とする。
Smart Images

Figure 2025506415000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0086337, filed with the Korean Intellectual Property Office on July 13, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode active material, a method for producing a negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is expanding more and more.
[0005] With the development of technology and increasing demand for mobile devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research on methods for manufacturing high-density electrodes with higher energy density per unit volume as electrodes for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode, and the negative electrode active material may be silicon-based particles having a large discharge capacity.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, while silicon-based compounds, which are high-capacity materials, have a larger capacity than conventionally used graphite, they have the problem that their volume expands rapidly during charging, cutting off the conductive path and degrading the battery characteristics.
[0008] In order to solve the problems when using silicon-based compounds as negative electrode active materials, various methods have been discussed, such as a method of controlling the driving potential, a method of additionally coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, a method of suppressing the volume expansion itself, or a method of preventing the conductive path from being broken. However, in the case of the above methods, there is a possibility that the performance of the battery may be deteriorated, so there is a limit to the application, and there is still a limit to the commercialization of the manufacture of negative electrode batteries with a high content of silicon-based compounds.
[0009] Therefore, even when a silicon-based active material is used as a negative electrode active material to improve capacity performance, research is needed into silicon-based active materials themselves that can prevent damage to the conductive path due to the volume expansion of the silicon-based compound. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]
[0011] When producing a silicon-based active material by a chemical processing method rather than a conventional grinding processing method, it has been found by research that the average particle size (D50) and crystal grains of the silicon-based active material can be adjusted within a predetermined range. By adjusting the crystal grains within the predetermined range, it was confirmed that during the insertion / desorption reaction of lithium, the reaction occurs uniformly and the stress received by the silicon-based active material is reduced.
[0012] The present application relates to a negative electrode active material, a method for manufacturing a negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode, which can solve the above problems.
Means for Solving the Problems
[0013] One embodiment of the present specification provides a negative electrode active material including a silicon-based active material having a crystal grain size of 200 nm or less, wherein the average particle size (D50) of the silicon-based active material is 1 μm or more and 9 μm or less, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) is included in an amount of 70 parts by weight or more.
[0014] In another embodiment, a method for manufacturing a negative electrode active material includes: chemically reacting silane gas to deposit a silicon-based active material on a substrate; and obtaining the silicon-based active material deposited on the substrate, wherein the crystal grain size of the silicon-based active material is 200 nm or less, and the average particle size (D50) of the silicon-based active material is 1 μm or more and 9 μm or less.
[0015] In another embodiment, a negative electrode composition including the negative electrode active material according to the present application, a negative electrode conductive material, and a negative electrode binder is provided.
[0016] In another embodiment, a negative electrode for a lithium secondary battery is provided, which includes a negative electrode current collector layer; and a negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer contains the negative electrode composition according to the present application or a cured product thereof.
[0017] Finally, a lithium secondary battery is provided, which includes a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
Advantages of the Invention
[0018] In the case of the negative electrode active material according to an embodiment of the present invention, unlike the conventional grinding processing method, it is produced by controlling the reaction conditions of a chemical method in which silane gas and an acid react with each other, thereby satisfying an average particle size (D50) and a crystal particle size within a predetermined range.
[0019] The negative electrode active material of the present invention, as a silicon-based active material, contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, it contains 70 parts by weight or more of the SiOx (x = 0), that is, while having a pure silicon (Pure Si) active material, the main feature is that the problem of volume expansion due to charge and discharge, which is a problem caused by this, is solved by adjusting the average particle size (D50) and the crystal particle size within a predetermined range.
[0020] In particular, the negative electrode active material according to the present application is characterized by controlling the average particle size (D50) and the crystal particle size of the silicon-based active material. Generally, when using a silicon-based active material with a large average particle size, the resistance of lithium ions moving through the pores in the electrode decreases. However, as the average particle size increases, lithium ions cannot penetrate to the inside of the particles, and a non-uniform lithium reaction occurs within the active material, resulting in a problem of reduced life characteristics. To improve this, when simply applying an active material with a small average particle size (D50) of the silicon-based active material, the reaction occurs uniformly throughout the internal region of the particles, but it is difficult to secure a lithium ion path in the electrode and the resistance increases, resulting in a problem of reduced long-term life performance.
[0021] In the present application, recognizing the above problems, the average particle size (D50) of the silicon-based active material in the negative electrode active material is adjusted to the above range, so that the lithium ion migration resistance of the electrode is not large and the reaction within the particles can occur uniformly. At the same time, the crystal grain size of the silicon-based particles is adjusted as above, so that the grain boundaries are widely distributed, and the lithium ions are more uniformly distributed during the insertion of lithium ions, so that the stress generated when the lithium ions are inserted into the silicon particles can be reduced, thereby alleviating the cracking of the particles, and finally, the life stability of the negative electrode can be further improved. [Brief description of the drawings]
[0022] [Figure 1] 1 shows an expanded view of a silicon-based active material according to one embodiment of the present application. [Diagram 2] FIG. 2 is a diagram showing a manufacturing process of a silicon active material according to Example 1 of the present application. [Diagram 3] FIG. 2 is a diagram showing a manufacturing process of a silicon active material according to Comparative Example 1 of the present application. [Figure 4] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 5] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. [Figure 6] FIG. 1 is a diagram showing a method for calculating grain size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Prior to describing the present invention, some terms will first be defined.
[0024] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0025] In this specification, "p to q" means "greater than or equal to p and less than or equal to q."
[0026] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area can mean the specific surface area measured by the above-mentioned measurement method.
[0027] In this specification, "Dn" means particle size distribution, and refers to the particle size at n% of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at 50% of the cumulative particle number distribution by particle size, D90 is the particle size at 90% of the cumulative particle number distribution by particle size, and D10 is the particle size at 10% of the cumulative particle number distribution by particle size. Meanwhile, the average particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and when the particles pass through a laser beam, the difference in the diffraction pattern due to the particle size is measured to calculate the particle size distribution.
[0028] In one embodiment of the present application, the particle size or grain size may refer to the average grain size or representative grain size of each grain constituting the metal powder.
[0029] In the present specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer participates in a polymerization reaction and is contained as a repeating unit in the polymer. In the present specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0030] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless specifically referred to as a "homopolymer".
[0031] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as the standard substance. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.
[0032] Hereinafter, with reference to the drawings, a detailed description will be given so that a person having ordinary knowledge in the technical field to which the present invention pertains can easily implement the present invention. However, the present invention can be embodied in various different forms and is not limited to the following description.
[0033] One embodiment of this specification provides a negative electrode active material containing a silicon-based active material having a crystal grain size of 200 nm or less, wherein the average particle size (D50) of the silicon-based active material is 1 μm or more and 9 μm or less, the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of the SiOx (x = 0).
[0034] The negative electrode active material of the present invention contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2) as the silicon-based active material, and based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of the SiOx (x = 0), that is, while having a pure silicon (Pure Si) active material, the main feature is that the problem of volume expansion due to charge and discharge, which is a problem thereof, is solved by adjusting the average particle size (D50) and the crystal grain size within a predetermined range.
[0035] Figure 1 shows an enlarged view of a silicon-based active material according to an embodiment of the present application. Specifically, the silicon-based active material 1 is composed of a number of crystal structures 2. At this time, it can be confirmed that the crystal structures have a crystal grain distribution of 1 nm or more and 200 nm or less. In addition, the space between crystal structures can be defined as a grain boundary. Usually, the crystal structure may also be expressed as crystal grains.
[0036] In one embodiment of the present application, the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be contained in an amount of 70 parts by weight or more.
[0037] In one embodiment of the present application, the silicon-based active material contains SiOx (x = 0). Based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be contained in an amount of 70 parts by weight or more.
[0038] In another embodiment, based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be contained in an amount of 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be contained in an amount of 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0039] In one embodiment of the present application, particularly, pure silicon (Si) particles may be used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material may mean, as described above, that pure Si particles (SiOx (x = 0)) not combined with other particles or elements are contained within the above range based on 100 parts by weight of the entire silicon-based active material.
[0040] In one embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.
[0041] According to one embodiment, the crystal grain size of the SiOx (x=0) may be 200 nm or less.
[0042] In one embodiment of the present application, the silicon-based active material may contain metal impurities. In this case, the impurities are metals that may be generally contained in silicon-based active materials, and specifically, the impurities may be contained in an amount of 0.1 parts by weight or less based on 100 parts by weight of the silicon-based active material.
[0043] Silicon-based active materials have a significantly higher capacity than conventional graphite-based active materials, and many attempts have been made to use them. However, they have a high volume expansion rate during charging and discharging, and so their use has been limited to mixing a small amount with a graphite-based active material.
[0044] Therefore, in the case of the present invention, in order to improve capacity performance, only a silicon-based active material is used as a negative active material, but in order to solve the above-mentioned problems, the average particle size (D50) and crystal particle size of the silicon-based active material itself are adjusted rather than adjusting the composition of the conductive material and binder.
[0045] In one embodiment of the present application, the silicon-based active material may have a crystal grain size of 200 nm or less.
[0046] In another embodiment, the crystal grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The crystal grain size of the silicon-based active material may be 1 nm or more, preferably 3 nm or more.
[0047] The silicon-based active material has the above-mentioned crystal grain size, and the crystal grain size of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process described below. At this time, by satisfying the above-mentioned range, the grain boundaries are widely distributed, and lithium ions enter uniformly during lithium ion insertion, and the stress applied during lithium ion insertion into silicon particles can be reduced, thereby alleviating particle cracking. As a result, the negative electrode has the characteristic of improving the life stability. If the crystal grain size exceeds the above-mentioned range, the grain boundaries within the particles are narrowly distributed, and in this case, lithium ions within the particles are non-uniformly inserted, and the stress due to ion insertion increases, causing particle cracking.
[0048] In one embodiment of the present application, there is provided a negative electrode active material, wherein the silicon-based active material includes a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less, and an area ratio of the crystalline structure is 5% or less based on the total area of the silicon-based active material.
[0049] In still another embodiment, the area ratio of the crystalline structure may be 5% or less, 3% or less, or 0.1% or more, based on the total area of the silicon-based active material.
[0050] That is, the silicon-based active material according to the present application has a crystal grain size of 200 nm or less, and the size of each crystal structure is small, so that the above-mentioned area ratio can be satisfied, and thus the distribution of grain boundaries can be broadened, thereby achieving the above-mentioned effects.
[0051] In one embodiment of the present application, there is provided a negative electrode active material, in which the number of crystal structures contained in the silicon-based active material is 20 or more.
[0052] The number of crystalline structures contained in the silicon-based active material may mean the number of each crystalline structure in Fig. 1. That is, the silicon-based active material itself may be composed of a plurality of crystalline structures, and in this case, the number of crystalline structures may be 20 or more.
[0053] In another embodiment, the number of crystalline structures contained in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may be in the range of 60 or less, or 50 or less.
[0054] That is, as described above, when the crystal grain size of the silicon-based active material satisfies the above range and the number of crystal structures satisfies the above range, the silicon-based active material itself has a suitable range of strength, and when contained in an electrode, it can impart flexibility and can efficiently suppress volume expansion.
[0055] In this application, the term "crystal grain" refers to a crystal grain in a metal or material that is composed of an irregularly shaped aggregate of microscopic sizes, and the term "crystal grain size" may refer to the grain size of the observed crystal grains. That is, in this application, the term "crystal grain size" refers to the size of a domain that shares the same crystal orientation within a grain, and has a different concept from the grain size or grain size that expresses the size of a substance.
[0056] In one embodiment of the present application, the crystal grain size can be calculated as a FWHM (Full Width at Half Maximum) value by XRD analysis. Specifically, a method for calculating the crystal grain size can be understood from FIG. 6. In FIG. 6, the remaining values except for L are measured by XRD analysis of the silicon-based active material, and the crystal grain size can be calculated by the Debye-Scherrer equation, which shows that FWHM and crystal grain size are inversely proportional to each other. At this time, the Debye-Scherrer equation is as shown in the following Equation 1-1.
[0057] [Formula 1-1] FWHM = (Kλ) / (LCOSθ)
[0058] In the above formula 1-1, L is the crystal grain size, K is a constant, θ is the Bragg angle, and λ is the wavelength of X-ray.
[0059] The shape of the crystal grains may be variously measured three-dimensionally, and the crystal grain size may be measured by a commonly used circle method or diameter measurement method, but is not limited thereto.
[0060] The diameter measurement method involves drawing 5 to 10 equilibrium lines, each with a length of L mm, on a micrograph of the target particle, and counting and averaging the number of crystal grains z on the lines. At this time, only those that are completely included are counted, and those that overlap are excluded. If the number of lines is P and the magnification is V, the average grain size can be calculated using the following formula 1-2. [Formula 1-2] Dm = (L*P*10 3 ) / (zV)(μm)
[0061] In addition, the circle method is a method in which a circle of a predetermined diameter is drawn on a micrograph of a target particle, and then the average area of the crystal grains is calculated based on the number of crystal grains that fall within the circle and the number of crystal grains that overlap the boundary, and can be calculated using the following formula 1-3. [Formula 1-3] Fm = (Fk * 10 6 ) / ((0.67n+z)V 2 )(μm 2 )
[0062] In the above formula 1-3, Fm is the average particle area, Fk is the measured area on the photograph, z is the number of particles that fit inside the circle, n is the number of particles that span the arc, and V is the magnification of the microscope.
[0063] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.
[0064] The silicon-based active material containing silicon-based particles having a particle size distribution of 0.01 μm to 30 μm means that the silicon-based active material contains a large number of individual silicon-based particles having particle sizes within the above range, and the number of silicon-based particles contained is not limited.
[0065] The particle size of the silicon-based particles may be expressed as their diameter when they are spherical, but when they are other shapes than spherical, the particle size may be measured in comparison with the spherical case, and the particle size of individual silicon-based particles may be measured by methods commonly used in the art.
[0066] Meanwhile, the average particle size (D50 particle size) of the silicon-based active material of the present invention is 1 μm or more and 9 μm or less, specifically, 2 μm to 8 μm, and more specifically, 3 μm to 8 μm. When the average particle size is within the above range, the specific surface area of the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. As a result, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the silicon-based active material has a value equal to or greater than the lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, and the capacity retention rate is increased. Meanwhile, when the average particle size satisfies the above range, the silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the phenomenon of non-uniform current density during charging and discharging.
[0067] In the present application, there is provided a negative electrode active material, wherein the silicon-based active material has a crystal grain size of 1 nm or more and 200 nm or less, and an average grain size (D50) of the silicon-based active material is 3 μm or more and 8 μm or less.
[0068] In particular, the negative electrode active material according to the present application is characterized by controlling the average particle size (D50) and crystal particle size of the silicon-based active material. It is generally known that when a silicon-based active material with a large average particle size is used, it is easy to secure a lithium ion path. However, as the average particle size increases, the adhesive strength with the negative electrode current collector layer decreases, which causes a problem of a rapid deterioration in life characteristics. Therefore, when an active material with a small average particle size (D50) of the silicon-based active material is simply applied, the life performance can be secured, but it is difficult to secure a lithium ion path, which causes a problem of increased resistance.
[0069] In the present application, recognizing the above problems, the negative electrode active material secures life characteristics by controlling the average particle size (D50) of the silicon-based active material within the above range, and also controls the crystal grain size of the silicon-based particles as described above to widely distribute the grain boundaries, so that lithium ions are uniformly inserted during lithium ion insertion, and the stress applied during lithium ion insertion in the silicon particles can be reduced, thereby mitigating particle cracking, resulting in improved life stability of the negative electrode.
[0070] In one embodiment of the present application, the silicon-based active material usually has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably less than 0.01 m 2 / g~150m 2 / g, more preferably 0.1m 2 / g~100m 2 / g, particularly preferably 0.2m 2 / g~80m 2 / g, most preferably 0.2m 2 / g~18m 2 / g. The BET specific surface area is determined according to DIN 66131 (using nitrogen).
[0071] In one embodiment of the present application, the silicon-based active material may be present, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or multi-lobed particles.Alternatively, the silicon particles may have a fibrous structure or may be present in the form of a silicon-containing thin film or coating, but less preferably.
[0072] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0073] In this application, the circularity is determined by the following formula 1-A, where A is the area and P is the perimeter.
[0074] [Formula 1-A] 4πA / P 2
[0075] In one embodiment of the present application, there is provided a negative electrode composition comprising: the negative electrode active material; a negative electrode conductive material; and a negative electrode binder.
[0076] In one embodiment of the present application, there is provided a negative electrode composition, in which the negative electrode active material is 40 parts by weight or more based on 100 parts by weight of the negative electrode composition.
[0077] In yet another embodiment, the negative electrode active material may contain, based on 100 parts by weight of the negative electrode composition, 40 parts by weight or more, preferably 60 parts by weight or more, more preferably 65 parts by weight or more, and even more preferably 70 parts by weight or more, and may contain 95 parts by weight or less, preferably 90 parts by weight or less, and more preferably 85 parts by weight or less.
[0078] The negative electrode composition according to the present application uses a negative electrode active material that satisfies a specific crystal grain size that can control the volume expansion rate during charging and discharging even when a negative electrode active material with a significantly high capacity is used within the above range, and is characterized by not reducing the performance of the negative electrode even when the negative electrode active material is contained within the above range, and by having excellent output characteristics during charging and discharging.
[0079] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but recently, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, there are some cases where the volume of the silicon-based active materials rapidly expands during charging / discharging, causing damage to the conductive path formed in the negative electrode active material layer.
[0080] Therefore, in one embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of dot-like conductive materials, sheet-like conductive materials, and linear conductive materials.
[0081] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of realizing high conductivity and excellent dispersibility.
[0082] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of 40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.
[0083] In one embodiment of the present application, the dot-shaped conductive material may have a functional group content (volatile matter) of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.
[0084] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, the functional group is present on the surface of the dot-shaped conductive material, and when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, by using a specific silicon-based active material in the present invention, the functional group content of the dot-shaped conductive material can be reduced, thereby having an excellent effect on improving dispersibility.
[0085] In one embodiment of the present application, the active material is characterized in that it contains a dot-shaped conductive material having a functional group content in the above range together with a silicon-based active material, and the functional group content can be adjusted by the degree of heat treatment of the dot-shaped conductive material.
[0086] In one embodiment of the present application, the particle size of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0087] In one embodiment of the present application, the conductive material may include a sheet-shaped conductive material.
[0088] The planar conductive material can increase surface contact between silicon particles in the negative electrode to improve conductivity, and at the same time, can suppress disconnection of the conductive path due to volume expansion. The planar conductive material may be referred to as a plate-type conductive material or a bulk-type conductive material.
[0089] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may preferably be platelet graphite.
[0090] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically, 3 μm to 6 μm, and more specifically, 3.5 μm to 5 μm. If the above range is satisfied, the particle size is sufficient, so that the viscosity of the negative electrode slurry is not increased too much, and dispersion is easy. Therefore, the dispersion effect is excellent when dispersing using the same device and time.
[0091] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.
[0092] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material with a high specific surface area or a sheet conductive material with a low specific surface area without any restrictions. In particular, the sheet conductive material in the present application may have electrode performance that is affected to some extent by dispersion, and it is particularly preferable to use a sheet conductive material with a low specific surface area in which dispersion problems do not occur.
[0093] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 1 m 2 / g or more.
[0094] In another embodiment, the sheet conductive material has a BET specific surface area of 1 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g.
[0095] The sheet conductive material according to the present application may be a sheet conductive material with a high specific surface area; or a sheet conductive material with a low specific surface area.
[0096] In another embodiment, the sheet conductive material is a sheet conductive material having a high specific surface area, and the BET specific surface area is 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0097] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of 1 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.
[0098] Alternatively, the conductive material may be a linear conductive material such as a carbon nanotube. The carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in which a plurality of carbon nanotube units are arranged in parallel with the longitudinal axis of the carbon nanotube units being substantially aligned in the same direction or twisted into a bundle or rope. The carbon nanotube unit has a graphite sheet having a nano-sized cylindrical shape and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure at which it is wound. The bundle-type carbon nanotube may be uniformly dispersed during the manufacture of the negative electrode compared to an entangled type carbon nanotube, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0099] In the present application, there is provided a negative electrode composition, in which the negative electrode conductive material is 20 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0100] In another embodiment, the negative electrode conductive material may be 20 parts by weight or less, 17 parts by weight or less, or 15 parts by weight or less, or may be 3 parts by weight or more, or 5 parts by weight or more, based on 100 parts by weight of the negative electrode composition.
[0101] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application plays a role of controlling the contact between the silicon-based active material, which has a very large volume expansion of the electrode due to charging and discharging, and the positive electrode conductive material plays a role of providing some conductivity while acting as a buffer for a shock-absorbing effect when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.
[0102] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0103] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of the carbon-based active material usually used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.
[0104] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, which may be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not serve to store and release lithium, but serves to ensure a planar conductive path within the negative electrode active material layer.
[0105] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-shaped form and used as a material to ensure a conductive path rather than to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.
[0106] Meanwhile, in the present application, the carbon-based active material being used as an active material means that it is processed into a dotted or spherical shape and used as a material that plays a role in storing or releasing lithium.
[0107] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, is dot-shaped and has a BET specific surface area of 0.1 m 2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, is planar and has a BET specific surface area of 5 m 2 / g or more.
[0108] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0109] The negative electrode binder according to one embodiment of the present application serves to control the active material and conductive material in order to prevent twisting and deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material. When the above-mentioned role is fulfilled, any conventional binder may be used, specifically, a water-based binder may be used, and more specifically, a PAM-based binder may be used.
[0110] In one embodiment of the present application, the amount of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, or may be 5 parts by weight or more, or 10 parts by weight or more.
[0111] One embodiment of the present application provides a method for manufacturing an anode active material, the method including: depositing a silicon-based active material on a substrate by chemically reacting a silane gas; and obtaining the silicon-based active material deposited on the substrate; wherein the silicon-based active material has a crystal grain size of 200 nm or less, and an average grain size (D50) of the silicon-based active material is 1 μm or more and 9 μm or less.
[0112] According to an embodiment of the present application, the method for preparing the negative active material may further include reacting silicon having a purity of 99% or more with an acid to form silane gas. In this case, the silicon having a purity of 99% or more may be referred to as MG-silicon (Metallurgical grade Si).
[0113] According to an embodiment, the silane gas may include one or more gases selected from monosilane, dichlorosilane, and trichlorosilane, and may be, specifically, trichlorosilane gas.
[0114] In one embodiment of the present application, the step of depositing a silicon-based active material on a substrate by chemically reacting the silane gas may be performed under a pressure condition of 10 Pa to 150 Pa. In this way, the silicon growth rate is reduced by the low pressure, and thus small crystal grains can be formed. The step may be performed under a temperature condition of 100° C. or more, specifically, 500° C. or more, preferably 800° C. or more, more preferably 800° C. to 1300° C., or 800° C. to 1100° C. This is a lower temperature than the conventional gas atomizing method in which the temperature is heated to 1600° C. or more to melt Si.
[0115] Conventionally, silicon-based active materials have been produced by crushing MG-silicon, which is a silicon lump, using physical force. When produced in this manner, the crystal grain size generally exceeds the range of 200 nm. Simply put, when producing silicon-based active materials using conventional methods, there is a drawback in that it is difficult to ensure the life stability of the negative electrode because the crystal grain size cannot be controlled.
[0116] However, in the method for producing the negative electrode active material according to the present application, as described above, silane is gasified and then deposited on a substrate through a chemical reaction, thereby forming silicon particles. Specifically, by modifying the temperature and pressure conditions in the process, a silicon-based active material that satisfies the crystal grain size according to the present application can be obtained.
[0117] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer comprising the negative electrode composition according to the present application or a cured product thereof, formed on one or both sides of the negative electrode current collector layer.
[0118] 4 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen. Although FIG. 4 shows that the negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer.
[0119] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of a negative electrode current collector layer, and drying the applied slurry.
[0120] In this case, the negative electrode slurry may include the negative electrode composition described above; and a slurry solvent.
[0121] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 40% or less.
[0122] In another embodiment, the solid content of the negative electrode slurry may be in the range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.
[0123] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, or may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0124] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, and the caking phenomenon of particles of the negative electrode composition is minimized, thereby enabling the negative electrode active material layer to be efficiently formed.
[0125] In one embodiment of the present application, the slurry solvent may be any solvent capable of dissolving the negative electrode composition, and specifically, water or NMP may be used.
[0126] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. In addition, the surface may be formed with fine irregularities to strengthen the binding force of the negative electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0127] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 5 μm or more and 500 μm or less.
[0128] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.
[0129] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.
[0130] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0131] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer, and in particular, the silicon-based active material and conductive material according to the present application are contained in specific compositions and content portions to satisfy the above range, thereby making it possible to provide an electrode having an appropriate range of electrical conductivity and resistance.
[0132] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0133] 2 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a lithium secondary battery anode 100 including an anode active material layer 20 on one side of an anode current collector layer 10 can be seen, and a lithium secondary battery cathode 200 including a cathode active material layer 40 on one side of a cathode current collector layer 50 can be seen, and the lithium secondary battery anode 100 and the lithium secondary battery cathode 200 are laminated with a separator 30 sandwiched therebetween.
[0134] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0135] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0136] In the positive electrode, the positive electrode current collector is not particularly limited as long as it is conductive without inducing chemical changes in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. Also, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0137] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0138] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.
[0139] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0140] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0141] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a coated separator containing a ceramic component or a polymeric material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.
[0142] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.
[0143] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0144] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0145] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents having a high dielectric constant and capable of dissociating lithium salts, and therefore can be preferably used. When such a cyclic carbonate is mixed with a linear carbonate having a low viscosity and a low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore such a cyclic carbonate can be more preferably used.
[0146] The metal salt may be a lithium salt, and the lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2- , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0147] In addition to the constituents of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in the capacity of the battery, and improving the discharge capacity of the battery.
[0148] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore may be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES
[0149] Below, preferred embodiments are presented to aid in understanding the present invention. However, these embodiments are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the claims.
[0150] (Production example) <Production of negative electrode active materials in Examples 1 to 8 and Comparative Examples 2 to 7> 2 is a diagram showing a manufacturing process of a silicon active material according to Example 1 of the present application. Specifically, a silicon block, MG-Si, was gasified with silane, and then chemically reacted and then deposited on a substrate to form a silicon-based active material. At this time, by controlling the process conditions (selecting conditions for adjusting the crystal grain size in Table 1 below within the temperature condition of 800°C to 1100°C and pressure condition of 10 Pa to 150 Pa range, and adjusting the temperature and pressure conditions to adjust the crystal grain size), the crystal grain size of the remaining silicon-based active materials of Examples 2 to 8 and Comparative Examples 2 to 7 can be controlled, and the results are shown in Table 1.
[0151] <Production of negative electrode active materials of Comparative Examples 1 and 8> 3 is a diagram showing the manufacturing process of silicon active materials according to Comparative Examples 1 and 8 of the present application. Specifically, silicon chunks, which are MG-Si, are pulverized by physical force, and the crystal grain size of the silicon-based active material at this time is as shown in Table 1.
[0152] [Table 1]
[0153] In Table 1, the average particle size (D50) of the silicon-based active material can be adjusted by varying the synthesis time of the silicon-based active material and the process time in the classification process. In particular, the silicon-based active material was prepared to satisfy the D50 in Table 1 by removing large particles and small particle regions in the classification process.
[0154] <Production of negative electrodes> The negative electrode active material including the silicon-based active material in Table 1, the conductive material, and polyacrylamide as a binder were added in a weight ratio of 80:10:10 to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry (solid concentration: 28 wt %).
[0155] Specifically, the conductive material is carbon black (specific surface area: 45 m 2 / g, diameter: 30 to 50 nm).
[0156] As a specific mixing method, the conductive material, binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the silicon-based active material was added and dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0157] The negative electrode current collector layer was prepared by applying the negative electrode slurry to one surface of a copper current collector (thickness: 15 μm) at a rate of 227 mg / 50 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm), which was used as a negative electrode (negative electrode thickness: 38 μm, negative electrode porosity: 40.0%).
[0158] <Secondary battery manufacturing> As the positive electrode active material, LiNi 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0159] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) on both sides of which the positive electrode slurry was applied at 537 mg / 25 cm. 2The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0160] A polyethylene separator was interposed between the positive electrode and the negative electrode of each of the examples and comparative examples, and an electrolyte was injected to prepare a lithium secondary battery.
[0161] The electrolyte was prepared by adding 3 wt % vinylene carbonate (based on the total weight of the electrolyte) to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) were mixed in a volume ratio of 10:90, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0162] <Experimental Example> Experimental example 1: Cycle life data The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention. The secondary batteries were subjected to an in-situ cycle test at 4.2-3.0V, 1C / 0.5C. During the test, the secondary batteries were charged / discharged at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and the capacity retention was measured.
[0163] Life retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at first cycle)} x 100
[0164] [Table 2]
[0165] As can be seen from Table 2, when checking the capacity retention rate according to the cycles of Examples 1 to 8 and Comparative Examples 1 to 8, it was confirmed that the capacity retention rates of Comparative Examples 1 to 8 were lower or the same as those of the Examples. This corresponds to the result that when a silicon-based active material is used in which the crystal grain size and the average grain size (D50) of the silicon-based active material satisfy the ranges according to the present invention, the lithium insertion and desorption reactions during charging and discharging can be uniformly reacted, the stress received by the silicon-based active material can be reduced, and the cracking of the particles can be alleviated, thereby improving the life retention rate of the electrode.
[0166] That is, by controlling the average particle size (D50) of the silicon-based active material within the above range, the lithium ion migration resistance of the electrode is not large, and the reaction can occur uniformly within the particles, and by controlling the crystal grain size of the silicon-based particles as above, the grain boundaries are widely distributed, and the lithium ions are more uniformly distributed during the insertion of lithium ions, and the stress generated during the insertion of lithium ions into the silicon particles can be reduced, thereby mitigating particle cracking. As a result, it has been confirmed that the negative electrode has the characteristic of being able to have a further improved life stability.
[0167] From the results of Experimental Example 1, it was confirmed that silicon-based active materials having specific crystal grains and a certain range of grain size have excellent life performance. When comparing Example with Comparative Examples 1 and 8, it was confirmed that as the crystal grain size increases, the stress generated during lithium insertion into the grain boundary increases, causing cracks in the active material and reducing life performance.
[0168] When the comparative examples 2 to 7 are compared with the examples, it can be seen that there is a difference in life performance depending on the particle size within a certain range. When the particle size is large as in the comparative examples 2 to 4, lithium cannot sufficiently penetrate into the active material, and a relatively large amount of stress is generated on the surface of the active material, causing cracks in the active material and resulting in a decrease in life performance. In addition, when the particle size is small as in the comparative examples 5 to 7, it can be seen that the life performance is decreased as the lithium ion migration resistance increases due to an increase in the lithium migration path during electrode manufacture, resulting in a decrease in life performance.
[0169] That is, it was confirmed that due to the influence of the crystal grain size and D50, the silicon-based active material having the crystal grain and grain size range (D50) within the optimum range as in the present application has excellent life performance.
[0170] Experimental example 2: Cycling resistance increase rate In the test of Experimental Example 1, the capacity retention was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at a pulse of 2.5C at SOC50, and the resistance increase rate was compared and analyzed.
[0171] For the measurement and evaluation of the resistance increase rate, data at 200 cycles was calculated, and the results are shown in Table 3 below.
[0172] [Table 3]
[0173] As can be seen from Table 3, after 200 cycles, the resistance increase rates of Comparative Examples 1 to 8 were higher than those of the Examples.
[0174] As can be seen from the results of Experimental Example 2, in the case of Examples 1 to 8 of the present invention, it was confirmed that the silicon-based active material having a specific crystal grain size within a certain range showed the lowest increase in resistance after cycling.
[0175] When comparing the Example with Comparative Examples 1 and 8, it was confirmed that as the crystal grain size increases, the stress generated during lithium insertion into the grain boundary increases, causing cracks in the active material, and as a result, the silicon-based active material is exposed to the electrolyte, causing side reactions, and the side reaction layer is stacked, increasing the resistance.
[0176] When comparing Comparative Examples 2 to 7 with the Examples, it was confirmed that there is a difference in life performance depending on the particle size within a specific range. As in Comparative Examples 2 to 4, when the particle size is large, lithium cannot sufficiently penetrate into the active material, and relatively large stress occurs on the surface of the active material, resulting in an increase in resistance due to the formation of a side reaction layer. Also, as in Comparative Examples 5 to 7, it was confirmed that when the particle size is small, the lithium ion migration resistance increases due to an increase in the lithium migration path during electrode manufacture.
[0177] In the end, it was confirmed that due to the influence of the crystal grain size and D50, the resistance increase rate of the silicon-based active material having the crystal grain and the grain size range (D50) within the optimal range as in the present application is excellent. [Explanation of symbols]
[0178] 1. Silicon-based active materials 2...Crystal structure 10 Negative electrode current collector layer 20...Negative electrode active material layer 30 Separator 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries A: Pulverization process using physical forces B: Chemical reaction process after silane gasification
Claims
1. Contains a silicon-based active material having a crystal grain size of 200 nm or less; The average particle size (D50) of the silicon-based active material is 1 μm or more and 9 μm or less, The silicon-based active material includes one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the silicon-based active material includes 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material.
2. 2. The negative electrode active material according to claim 1, wherein the crystal grain size of the SiOx (x=0) is 200 nm or less.
3. The negative electrode active material according to claim 1 , wherein the silicon-based active material includes a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less.
4. The crystal grain size of the silicon-based active material is 1 nm or more and 200 nm or less, The negative electrode active material according to claim 1 , wherein the silicon-based active material has an average particle size (D50) of 3 μm or more and 8 μm or less.
5. chemically reacting the silane gas to deposit a silicon-based active material on the substrate; and obtaining the silicon-based active material deposited on the substrate; A method for producing a negative electrode active material, comprising: The crystal grain size of the silicon-based active material is 200 nm or less, The method for producing a negative electrode active material according to any one of claims 1 to 4, wherein the silicon-based active material has an average particle size (D50) of 1 µm or more and 9 µm or less.
6. The method for producing a negative electrode active material according to claim 5 , wherein the silane gas contains one or more gases selected from monosilane, dichlorosilane, and trichlorosilane.
7. 6. The method of claim 5, wherein the step of depositing the silicon-based active material on the substrate by chemically reacting the silane gas is performed under a pressure condition of 10 Pa to 150 Pa.
8. The negative electrode active material according to any one of claims 1 to 4; A negative electrode conductive material; and Negative electrode binder; A negative electrode composition comprising:
9. The negative electrode composition according to claim 8 , wherein the negative electrode active material is present in an amount of 40 parts by weight or more based on 100 parts by weight of the negative electrode composition.
10. The negative electrode composition according to claim 8 , wherein the negative electrode conductive material is present in an amount of 20 parts by weight or less based on 100 parts by weight of the negative electrode composition.
11. a negative electrode current collector layer; and a negative electrode active material layer provided on one or both sides of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to claim 8 or a cured product thereof.
12. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 12. The negative electrode for a lithium secondary battery according to claim 11, wherein the negative electrode active material layer has a thickness of 5 μm or more and 500 μm or less.
13. positive electrode; The negative electrode for a lithium secondary battery according to claim 11 ; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery negative electrode material, and nonaqueous electrolyte secondary battery using the same
JP2009224168A
Lithium secondary battery and its manufacturing method
JP2009245773A
Method for producing negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2012221758A
Silicon-containing particle, negative electrode material of non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
JP2014170702A
Lithium rechargeable battery and method for manufacturing the same
WO2007114168A1